2008
DOI: 10.1152/ajpcell.00329.2007
|View full text |Cite
|
Sign up to set email alerts
|

Increasing α7β1-integrin promotes muscle cell proliferation, adhesion, and resistance to apoptosis without changing gene expression

Abstract: Liu J, Burkin DJ, Kaufman SJ. Increasing ␣7␤1-integrin promotes muscle cell proliferation, adhesion, and resistance to apoptosis without changing gene expression. Am J Physiol Cell Physiol 294: C627-C640, 2008. First published November 28, 2007 doi:10.1152/ajpcell.00329.2007.-The dystrophin-glycoprotein complex maintains the integrity of skeletal muscle by associating laminin in the extracellular matrix with the actin cytoskeleton. Several human muscular dystrophies arise from defects in the components of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
56
1
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 74 publications
(64 citation statements)
references
References 80 publications
6
56
1
1
Order By: Relevance
“…Thus, in the KO CMs vs. controls, the localization changed, but the total amount of α7 integrin did not. Previous studies in skeletal muscle have shown that the α7-integrin subunit can be retained in the endoplasmic reticulum when there is an excess of protein (45,46). We suggest that this occurs in the Tln2KO CMs.…”
Section: Discussionmentioning
confidence: 51%
“…Thus, in the KO CMs vs. controls, the localization changed, but the total amount of α7 integrin did not. Previous studies in skeletal muscle have shown that the α7-integrin subunit can be retained in the endoplasmic reticulum when there is an excess of protein (45,46). We suggest that this occurs in the Tln2KO CMs.…”
Section: Discussionmentioning
confidence: 51%
“…Integrin alpha 7 codes for a transmembrane protein of skeletal and cardiac muscle that links the cytoskeleton to the extracellular matrix. In C2C12 myoblasts, elevated levels of integrin result in increased adhesion to laminin, when serum is limiting [62]. Upregulation of integrin alpha 7 mediates cytoskeletonmembrane-extracellular matrix interactions [63].…”
Section: Discussionmentioning
confidence: 99%
“…26,27 Conversely, the downregulation of ITGA7 modulates interactions between integrins and the extracellular matrix such that fibronectin binding is favored. 27 In mammary epithelial cells, fibronectin-dependent signaling has been shown to upregulate c-Myc expression through the activation of the MEK-ERK pathway.…”
Section: Discussionmentioning
confidence: 99%